THE RELATIONSHIP BETWEEN GRATITUDE AND THE MEANING OF LIFE IN STUDENTS OF BHAYANGKARA JAKARTA RAYA UNIVERSITY - Sulistio, Rommy; Fitriyana, Rika; Utama Afriyenti, Lenny (Indonesian Journal of Social Work, 2024)
Abstract This study aims to determine whether there is a relationship between the two variables in students, with a total of 122 respondents from University Bhayangkara. The method used in this study is correlational with convenience sampling technique. To see the relationship of the two variables studied, using SPSS version 22. The results obtained show that gratitude is positively related to the meaning of life in University Bhayangkara students with a correlation value of 0.617**. So it can be concluded that the higher the meaning of life, the higher the sense of gratitude.